Solid electrolyte and preparation method and application thereof
By mixing carboxymethylcellulose lithium, polyethylene oxide, polyvinylpyrrolidone and ceramic powder to form a composite electrolyte membrane, and soaking in lithium salt solution, the dispersion, interface compatibility and long-term stability of composite solid electrolyte in preparation and application is solved, and a solid electrolyte with high ionic conductivity and capacity retention is achieved.
Patent Information
- Application Number
- CN202411792371.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-07
- Publication Date
- 2025-04-01
AI Technical Summary
Composite solid electrolytes face problems such as dispersion, interface compatibility and long-term stability in preparation and application, and there are still challenges in large-scale production and application.
By mixing and gelling carboxymethylcellulose lithium, polyethylene oxide, polyvinylpyrrolidone and ceramic powder, a composite electrolyte membrane is formed and soaked in a lithium salt solution to improve ionic conductivity and stability.
It improves the ionic conductivity and capacity retention of solid electrolytes, enhances interface stability, and simplifies the preparation process, making it easy to achieve large-scale production.
Smart Images

Figure CN119742433A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new material energy storage technology, and in particular to a solid electrolyte and a preparation method and application thereof. Background Art
[0002] The rapid development of portable electronic devices and electric vehicles has led to an increasing demand for high-performance batteries. Traditional liquid lithium-ion batteries are widely used in various fields due to their high energy density and long cycle life. However, the use of liquid electrolytes brings safety hazards such as leakage, flammability, and thermal runaway, which limits its further development in high energy density and high safety applications.
[0003] Solid electrolytes are considered to be a strong candidate for improving battery safety due to their non-flammable, non-corrosive and non-volatile properties. Solid electrolytes mainly include three categories: polymers, oxides and sulfides. Polymer electrolytes have good flexibility and processing properties, but low room temperature ionic conductivity; oxide electrolytes have high ionic conductivity and good thermal stability, but poor interfacial compatibility with electrode materials; sulfide electrolytes have attracted attention due to their high ionic conductivity, but their chemical stability and mechanical properties need to be improved.
[0004] In order to overcome the limitations of a single type of solid electrolyte, composite solid electrolytes have emerged. This electrolyte combines an inorganic solid electrolyte with a polymer matrix, aiming to take advantage of their respective strengths and improve the overall performance of the battery. The research on composite solid electrolytes has become a hot topic in the field of solid-state batteries, with the goal of achieving high ionic conductivity, excellent interface stability, and good mechanical properties.
[0005] Although some progress has been made in existing research, the preparation and application of composite solid electrolytes still face many challenges. For example, the dispersibility of inorganic fillers in polymer matrices, interfacial compatibility, and stability during long-term cycles have not been effectively solved. In addition, how to achieve large-scale production and application of composite solid electrolytes is also the focus of current research.
[0006] In recent years, patent applications for solid electrolytes have shown a rapid growth trend worldwide, demonstrating the research activity and technological progress in this field. However, patent analysis shows that despite certain progress in material design and preparation processes, research on the interface engineering and long-term stability of composite solid electrolytes is still insufficient. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention
[0007] The purpose of the present invention is to provide a solid electrolyte and a preparation method and application thereof.
[0008] In a first aspect, the present invention provides a method for preparing a solid electrolyte, comprising: mixing lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder, gelling and coating to form a film, soaking in a lithium salt solution and drying to obtain a solid electrolyte.
[0009] The preparation method provided by the present invention embeds polyvinyl pyrrolidone in a solid film in advance, and partially swells the polyvinyl pyrrolidone by immersing it in a lithium salt solution, so that the lithium solute in the lithium salt solution enters and solidifies in the solid film. At the same time, the addition of polyvinyl pyrrolidone can reduce the crystallinity of polyethylene oxide and increase the ionic conductivity, so that the capacity retention rate of the solid electrolyte can be comprehensively improved. In addition, the preparation method provided by the present invention is simple to operate, does not require the use of special equipment, and is easy to achieve planned production.
[0010] Optionally, after the carboxymethyl cellulose lithium, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder are mixed, the mass percentage of the polyethylene oxide is 50%-60%.
[0011] Optionally, the mass percentage of the lithium carboxymethyl cellulose is 18%-20%.
[0012] Optionally, after the carboxymethyl cellulose lithium, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder are mixed, the mass percentage of the polyvinyl pyrrolidone is 3%-5%.
[0013] Optionally, after the carboxymethyl cellulose lithium, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder are mixed, the mass percentage of the ceramic powder is 20%-25%.
[0014] Optionally, after lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder are mixed, the ceramic powder includes LLZTO ceramic powder.
[0015] Optionally, the preparation method of lithium carboxymethyl cellulose comprises: reacting carboxymethyl cellulose with lithium hydroxide in a solvent environment, followed by separation and drying to obtain lithium carboxymethyl cellulose.
[0016] Optionally, the molar ratio of the carboxymethyl cellulose to the lithium hydroxide is 1:(1.2-1.5).
[0017] Optionally, the carboxymethyl cellulose is prepared by reacting sodium carboxymethyl cellulose with hydrochloric acid.
[0018] Optionally, the solvent environment is a mixture of ethanol and water.
[0019] Optionally, the concentration of lithium hydroxide in the solvent environment is 5 mg / mL-10 mg / mL.
[0020] Optionally, the method comprises the following steps: mixing lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder in ultrapure water to prepare an electrolyte gel; coating the electrolyte gel into a film and then drying it to prepare a composite electrolyte membrane; and soaking the composite electrolyte membrane in a lithium salt solution and then drying it to prepare a solid electrolyte.
[0021] Alternatively, lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder are stirred and mixed in ultrapure water at a solid-liquid ratio of 0.04 g / mL to 0.05 g / mL.
[0022] Optionally, lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone, ceramic powder and ultrapure water are stirred and mixed at 20°C-30°C.
[0023] Optionally, the electrolyte gel is coated into a gel film with a thickness of 2000 μm-2200 μm.
[0024] Optionally, the electrolyte gel is coated into a film and then dried at 45° C.-50° C. to obtain a composite electrolyte membrane.
[0025] Alternatively, the electrolyte gel is coated on polytetrafluoroethylene to form a film.
[0026] Optionally, the electrolyte gel is coated into a film and then dried and shaped to obtain a composite electrolyte membrane.
[0027] Optionally, the composite electrolyte membrane has a thickness of 35 μm-55 μm.
[0028] Optionally, the lithium solute in the lithium salt solution includes lithium trisbisfluoromethylsulfonyl imide.
[0029] Optionally, the solvent in the lithium salt solution includes dimethyl carbonate.
[0030] Optionally, the concentration of lithium solute in the lithium salt is 0.5 mol / L-1.5 mol / L.
[0031] Optionally, the composite electrolyte membrane is immersed in the lithium salt solution.
[0032] Optionally, the composite electrolyte membrane is immersed in the lithium salt solution for 5 h to 8 h.
[0033] Optionally, the composite electrolyte membrane is preheated by vacuum drying at 55° C.-65° C.
[0034] In a second aspect, the present invention also provides a solid electrolyte prepared by any of the above optional preparation methods.
[0035] In a third aspect, the present invention also provides the application of the solid electrolyte prepared by any of the above optional preparation methods in the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 A flowchart of a method for preparing a solid electrolyte provided by the present invention;
[0037] Figure 2 The Nyquis diagram of the impedance test after the solid electrolyte prepared in Example 1 of the present invention is assembled into a button-type battery of gasket-solid electrolyte-gasket clamping;
[0038] Figure 3 The solid electrolyte prepared in Example 1 of the present invention is combined with a lithium iron phosphate positive electrode and a lithium metal negative electrode into a button-type half-cell, and the cycle test curve at a charge and discharge rate of 0.1C;
[0039] Figure 4 The solid electrolyte prepared in Example 1 of the present invention is combined with a lithium iron phosphate positive electrode and a lithium metal negative electrode into a button-type half-cell, and the cycle test curve at a 1C charge and discharge rate is shown. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0041] The present invention provides a method for preparing a solid electrolyte, comprising: mixing carboxymethyl cellulose lithium, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder, coating the mixture into a film after gelation, and soaking the mixture in a lithium salt solution and drying the mixture to obtain a solid electrolyte. In fact, after polyethylene oxide and polyvinyl pyrrolidone are mixed, the polyvinyl pyrrolidone can reduce the cleanliness of polyethylene oxide, thereby increasing the ionic conductivity, and at the same time, the swelling property of polyvinyl pyrrolidone can promote the lithium solute in the lithium salt solution to enter the gel film, thereby further improving the ionic conductivity.
[0042] In some embodiments, after lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder are blended, the mass percentage of polyethylene oxide is 50%-60%. In fact, polyethylene oxide (PEO) can provide ion transmission channels in the gel film, and can complex with lithium salt solutes to promote the dissociation of lithium salts, and can also improve the mechanical properties and structural stability of the gel film.
[0043] Specifically, after carboxymethyl cellulose lithium, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder are blended, the mass percentage of carboxymethyl cellulose lithium (CMC-Li) is 18%-20%, and the mass percentage of polyvinyl pyrrolidone (PVP) is 3%-5%. In addition, the mass percentage of ceramic powder is 20%-25%, and the ceramic powder includes LLZTP ceramic powder.
[0044] In some embodiments, the preparation method of lithium carboxymethyl cellulose includes: reacting carboxymethyl cellulose with lithium hydroxide in a solvent environment, separating and drying to obtain lithium carboxymethyl cellulose. Specifically, the solvent environment used is a mixture of ethanol and water, so that the carboxymethyl cellulose and lithium hydroxide can be fully dissolved.
[0045] In addition, when preparing lithium carboxymethyl cellulose, the molar ratio of carboxymethyl cellulose to lithium hydroxide is 1:(1.2-1.5). By setting the lithium hydroxide in excess, it is helpful to improve the conversion rate of carboxymethyl cellulose and the yield of lithium carboxymethyl cellulose. At the same time, the concentration of lithium hydroxide in the solvent environment during the reaction is 5mg / mL-10mg / mL.
[0046] Specifically, see Figure 1 , the preparation method of the solid electrolyte comprises the following steps:
[0047] S1, mixing lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder in ultrapure water to prepare an electrolyte gel;
[0048] S2, coating the electrolyte gel into a film and drying it to obtain a composite electrolyte membrane;
[0049] S3. Soak the composite electrolyte membrane in a lithium salt solution and then dry it to obtain a solid electrolyte.
[0050] In some embodiments, in step S1, lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder are added to ultrapure water at a solid-liquid ratio of 0.04 g / mL-0.05 g / mL and stirred and mixed. Specifically, by controlling the dosage ratio, the fluidity and gel properties of the electrolyte gel can be adjusted, which is helpful for coating the electrolyte gel into a film.
[0051] In some embodiments, in step S1, lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder can be added to ultrapure water at room temperature of 20° C. to 30° C. for stirring and mixing. In addition, in order to improve the mixing uniformity, ultrasonic treatment can be performed to improve the dispersion uniformity of the ceramic powder therein, thereby improving the uniformity of the prepared electrolyte gel.
[0052] In some embodiments, in step S2, the electrolyte gel is coated into a gel film with a thickness of 2000 μm-2200 μm. In fact, the electrolyte gel can be coated into a film by a gel coating method commonly used in the art, such as roller coating, brush coating, etc. In addition, after the gel film is obtained, it can be dried in an environment of 45°C-50°C to obtain a composite electrolyte membrane, and the thickness of the composite electrolyte membrane is 35μm-55μm.
[0053] In some embodiments, in step S2, the electrolyte gel may be coated on polytetrafluoroethylene to form a film, which helps to improve the cleanliness of the composite electrolyte membrane and improve the convenience of peeling off the composite electrolyte membrane.
[0054] In some embodiments, in step S3, the lithium solute in the lithium salt solution includes lithium tris(bis(fluoromethylsulfonyl)imide) at a concentration of 0.5 mol / L-1.5 mol / L, and the solvent used in the lithium salt solution includes dimethyl carbonate. In addition, in step S3, the composite electrolyte membrane is immersed in the lithium salt solution for 5 h-8 h to partially swell the polyvinyl pyrrolidone and promote the lithium solute to enter the composite electrolyte membrane. At the same time, the composite electrolyte membrane can be dried and preheated in a vacuum environment at 55°C-65°C before immersion.
[0055] The present invention also provides a solid electrolyte prepared by the preparation method in any of the above embodiments.
[0056] The present invention also provides an application of a solid electrolyte prepared by the preparation method in any of the above embodiments in the field of energy storage.
[0057] Preparation Example 1
[0058] This preparation example 1 provides a LLZTO (Li 6.4 LqCy 1.4 Ta 0.6 O 12 ) A method for preparing ceramic powder, comprising the following steps: based on Li 6.4 LqCy 1.4 Ta 0.6 O 12 LiOH·H2O, La2O3, ZrO2 and Ta2O5 were weighed, ball-milled at a speed of 500 rpm for 12 hours, and then stirred and mixed with isopropanol to obtain a composite slurry; the composite slurry was dried at 60°C for 12 hours to constant weight to obtain a precursor coarse powder; the precursor coarse powder was calcined at 900°C in a magnesia crucible for 6 hours and then ground to obtain a precursor fine powder; the precursor fine powder was pressed into an embryo with a diameter of 15 mm under a pressure of 10 MPa, and the embryo was calcined at 1200°C for 6 hours, then crushed and ground to obtain LLZTO ceramic powder with a D50 of 1.4 μm.
[0059] Example 1
[0060] This embodiment 1 provides a method for preparing a solid electrolyte, comprising the following steps:
[0061] S1. Add 0.16 g of lithium carboxymethyl cellulose (CMC-Li), 0.03 g of polyvinyl pyrrolidone (PVP, K30, purchased from Tapico), and 0.5 g of polyethylene oxide (PEO, purchased from Aladdin) into 20 mL of ultrapure water, stir magnetically for 8 h, then add 0.2 g of the LLZTO ceramic powder prepared in Preparation Example 1, stir magnetically for 4 h, and then stand for 8 h to prepare an electrolyte gel;
[0062] S2. Use a scraper with a height of 2000 μm to coat the electrolyte gel on a polytetrafluoroethylene plate, dry it in a vacuum oven at 45°C for 5 hours, and then use a punching machine to punch out a composite electrolyte membrane with a diameter of 19 mm;
[0063] S3. The composite electrolyte membrane was dried in a vacuum oven at 60°C for 6 hours and then quickly transferred to a glove box. In the glove box, 1.435 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI, purchased from Jiujiang Tianci) was weighed and dissolved in 10 mL of dimethyl carbonate to prepare a lithium salt solution with a concentration of 1 mol / L. The composite electrolyte membrane was then immersed in the lithium salt solution for 12 hours, and then the composite electrolyte membrane was taken out and dried in the glove box for 6 hours to obtain a solid electrolyte.
[0064] Performance Testing
[0065] The solid electrolyte prepared in Example 1 was combined with two gaskets with a specification of 15.8 mm × 1 mm and a spring to form a button-type half-cell, and 5 μL of lithium hexafluorophosphate electrolyte was used to improve the solid-solid interface contact problem. The EIS impedance test was carried out on the Chenhua electrochemical workstation, and its Nyquis diagram was as follows: Figure 2 As shown;
[0066] The solid electrolyte prepared in Example 1 was combined with a lithium iron phosphate positive electrode and a lithium metal negative electrode (purchased from Beijing Inokai Company and cut into lithium sheets with a diameter of 16) to form a button half-cell. Note that 5 μl of lithium hexafluorophosphate electrolyte was used to improve the solid-solid contact problem. Electrochemical tests were performed on a Xinwei battery tester at charge and discharge rates of 0.1C and 1C, respectively. The cycle test curves are shown in FIG. Figure 3 and Figure 4 shown.
[0067] from Figure 2 It can be seen from the figure that the impedance of the solid electrolyte prepared in Example 1 is about 1125Ω, and Figure 3 and Figure 4It can be seen that at a rate of 0.1C, the initial charge and discharge capacity is 172.38 mAh / g, its coulombic efficiency is close to 100%, and the capacity retention rate after 80 cycles is 87%. At a rate of 1C, the initial charge and discharge capacity is 101 mAh / g, its coulombic efficiency is also close to 100%, and the capacity retention rate after 80 cycles is 91%.
[0068] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A method for preparing a solid electrolyte, characterized in that: include: Carboxymethyl cellulose lithium, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder are mixed and gelled, then coated into a film, immersed in a lithium salt solution and dried to obtain a solid electrolyte.
2. The preparation method according to claim 1, characterized in that: After mixing lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder, wherein: the mass percentage of the polyethylene oxide is 50%-60%; and / or, the mass percentage of the lithium carboxymethyl cellulose is 18%-20%; and / or, the mass percentage of the polyvinyl pyrrolidone is 3%-5%; and / or, the mass percentage of the ceramic powder is 20%-25%; and / or, the ceramic powder includes LLZTO ceramic powder.
3. The preparation method according to claim 1, characterized in that: The preparation method of lithium carboxymethyl cellulose comprises: reacting carboxymethyl cellulose with lithium hydroxide in a solvent environment, separating and drying the reactants to obtain lithium carboxymethyl cellulose.
4. The preparation method according to claim 3, characterized in that: The molar ratio of the carboxymethyl cellulose to the lithium hydroxide is 1:(1.2-1.5); and / or the carboxymethyl cellulose is prepared by reacting sodium carboxymethyl cellulose with hydrochloric acid; and / or the solvent environment is a mixture of ethanol and water; and / or the concentration of lithium hydroxide in the solvent environment is 5mg / mL-10mg / mL.
5. The preparation method according to claim 1, characterized in that: The method comprises the following steps: mixing carboxymethyl cellulose lithium, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder in ultrapure water to obtain electrolyte gel; coating the electrolyte gel into a film and drying it to obtain a composite electrolyte membrane; and soaking the composite electrolyte membrane in a lithium salt solution and drying it to obtain a solid electrolyte.
6. The preparation method according to claim 5, characterized in that: Lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone and ceramic powder are stirred and mixed in ultrapure water at a solid-liquid ratio of 0.04 g / mL-0.05 g / mL; and / or lithium carboxymethyl cellulose, polyethylene oxide, polyvinyl pyrrolidone, ceramic powder and ultrapure water are stirred and mixed at 20°C-30°C.
7. The preparation method according to claim 5, characterized in that: The electrolyte gel is coated into a gel film with a thickness of 2000 μm-2200 μm; and / or, the electrolyte gel is coated into a film and then dried at 45° C.-50° C. to obtain a composite electrolyte membrane; and / or, the electrolyte gel is coated on polytetrafluoroethylene to form a film; And / or, the electrolyte gel is coated into a film and then dried and shaped to obtain a composite electrolyte membrane; and / or, the thickness of the composite electrolyte membrane is 35 μm-55 μm.
8. The preparation method according to claim 5, characterized in that: The lithium solute in the lithium salt solution includes lithium trisbisfluoromethylsulfonyl imide; and / or, the solvent in the lithium salt solution includes dimethyl carbonate; and / or, the concentration of the lithium solute in the lithium salt is 0.5 mol / L-1.5 mol / L; and / or, the composite electrolyte membrane is immersed in the lithium salt solution; and / or, the composite electrolyte membrane is soaked in the lithium salt solution for 5h-8h; and / or, the composite electrolyte membrane is preheated by vacuum drying at 55°C-65°C.
9. A solid electrolyte prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the fixed electrolyte prepared by the preparation method according to any one of claims 1 to 8 in the field of energy storage.
Citation Information
Cited By
Composition for diaphragm, diaphragm as well as preparation method and application of diaphragm
CN120432810A